Wavelength multicasting quantum clock synchronization network - Jiaao Li; Hui Han; Xiaopeng Huang; Bangying Tang; Kai Guo; Jinquan Huang; Siyu Xiong; Wanrong Yu; Zhaojian Zhang; Junbo Yang; Bo Liu; Huan Chen; et al. (AAPPS Bulletin)
Abstract Quantum clock synchronization (QCS) can measure out the high-precision clock difference among distant users, which breaks through the standard quantum limit by employing the properties of quantum entanglement. Currently, the wavelength division multiplexed QCS network has been demonstrated with a spontaneous parametric down-conversion entangled photon source. In this paper, we propose a more efficient QCS network scheme with the wavelength multicasting entangled photon source, which can decrease at least 25% of wavelength channel consumption under the identical network scale. Afterwards, a four node QCS network is demonstrated, where the wavelength multicasting entangled photon source is utilized with dual-pumped four-wave mixing silicon chip. The experimental results show that the measured time deviation is 3.4 ps with an average time of 640 s via the multiple fiber links of more than 10 km.